Financial literacy and the gains from financial experience learning by doing - Cuesta, Jowan Sebastian A. (School of Economics, University of the Philippines Diliman, 2018)
The purpose of this study is to determine whether a UP student_s exposure to the financial market and his acquired financial experience is associated with financial literacy. The study takes into account a student_s personal background, family socioeconomic background, and financial socialization to evaluate his exposure to the financial market and analyze the effects of financial experience and other factors that may affect his financial literacy. An ordered logit analysis was used to assess the effects of multiple variables divided among the given categories. Personal background details were generally not significant to financial literacy other than the birth order. Not being the first born shows positive association with financial literacy as explained by how one learns from the elder sibling. A family_s socioeconomic background generally had no significant effect on financial literacy, whether it be income or field of work. A student_s financial socialization has also shown varying effects on financial literacy. Credit card use is surprisingly negatively associated to financial literacy, while the use of mobile money or wallets is positively associated with financial literacy as the latter provides a more accurate measure of an active financial participation, and thus, greater financial experience. Having personally invested in the financial market has a positive association to financial literacy which further shows the effects of active financial participation leading to financial literacy. The study concludes that not a single factor is responsible for an increase in financial literacy and that the act of _learning by doing_, which includes financial market experience, active participation, combined with exposure and attitudinal aspects, is highly associated and effective in increasing financial literacy.